Sie sind auf Seite 1von 12

Math 334

6.3. INVERSE LAPLACE TRANSFORMS

90

theorem we get

L [cos ax ] =

1

− 2 πs
2 πs

1 e

a

2 π

0

a

e sx cos ax dx =

=

2

π

 

1

e

sx

 


2 πs

s 2 +

a 2 ( a sin

1

e

a

 

2 πs

 

1

a

( s ) ( s )

 

e

2 πs

s 2 + a 2

1

e

a

ax s cos ax )

0

a

=

s
s

s 2 + a 2 .

Example 6.23.

Finf L [f ( x )] for the function

f ( x ) =

1 0 < x 1

2

1 1 < x

,

f ( x

+ 2 n) = f ( x ) n Z .

Solution The function f is periodic with period 2, so we have

L[f ( x )] =

=

e 2s 2

1

0

1

e sx f ( x ) dx =

1

e 2s 2 e s + 1

s

1 e 2s

e 2s 1

1

0

1

e sx dx 2 e sx dx

1

=

(1 e s ) 2

1 e s

e s/ 2 e s/ 2

2 ) = 1 s tanh( 1 s ) .

s ( e s/ 2 + e s/

s (1 e 2s ) = s (1 + e s =

6.3 Inverse Laplace Transforms

s (1 + e − s = 6.3 Inverse Laplace Transforms Recall the solution procedure outlined

Recall the solution procedure outlined in Figure 6.1. The final stage in that solution procedure involves calulating inverse Laplace transforms. In this section we look at the problem of finding inverse Laplace transforms. In other words, given F ( s ), how do we find f ( x ) so that F ( s ) = L [f ( x )].

We begin with a simple example which illustrates a small prob lem on finding inverse Laplace transforms.

Example 6.24. Consider the functions

f ( x ) = x 2 ,

and

g ( x ) =

  x 2

48

π

x = 2 , 3

x = 2

x = 3

.

Then L [f ( x )] = L [g ( x )] = 2 3 . Since an integral is not affected by the changing of its integ rand at a few

s

isolated points, more than one function can have the same Lap lace transform.

more than one function can have the same Lap lace transform. Example 6.24 illustrates that inverse

Example 6.24 illustrates that inverse Laplace transforms a re not unique. However, it can be shown that, if several functions have the same Laplace transform, then at most one of them is continuous. This prompts us to make the following definition.

Definition 6.25. The inverse Laplace transform of F ( s ), denoted L 1 [F ( s )], is the function f defined on [0 , ) which has the fewest number of discontinuities and satisfie s

L [f ( x )] = F ( s ) .

Math 334

6.3. INVERSE LAPLACE TRANSFORMS

91

Example 6.26.

1.

2.

2

L 1 [ 3 ] = x 2 .

s

L 1 [

s

+ 9 ] = cos 3 x .

s

2

3.

s 1

s 2 2 s + 5 ] = L 1 [

1 s 2 − 2 s + 5 ] = L − 1 [ L −

L 1 [

6.17 in reverse)

s 1 ( s 1) 2

+ 4 ] = e x L 1 [

s

2

s + 4 ] = e x cos 2 x .

(using property 1 of Theorem

The inverse Laplace transform is a linear operator.

Theorem 6.27.

If L 1 [F ( s )]

and L 1 [G ( s )] exist, then L 1 [αF ( s ) + βG ( s )] = αL 1 [F ( s )] + β L 1 [G ( s )].

Proof Starting from the right hand side we have

L [αL 1 [F ( s )] + β L 1 [G ( s )]] = αL [L 1 [F ( s )]] + β L [L 1 [G ( s )]] = αF ( s ) + βG ( s ) .

The result follows.

)]] = αF ( s ) + βG ( s ) . The result follows. Most

Most of the properties of the Laplace transform can be revers ed for the inverse Laplace transform.

Theorem 6.28.

If L 1 [F ( s )] = f ( x ) , then the following hold:

1. L 1 [F ( s + a)] = e ax f ( x ) ;

2. L 1 [sF ( s )] = f ( x ) , if f (0) = 0 ;

3. L 1 [ 1 s F ( s )] = x f ( t ) dt ;

0

4. L 1 [e as F ( s )] = u a ( x ) f ( x a) .

Proof

1. L [e ax f ( x )] = F ( s + a)

2. L [f ( x ))] = f (0) + sF ( s ) from Theorem 6.17, property 4. The result follows.

from Theorem 6.17, property 1. The result follows.

3. L [ x f ( t ) dt ] = 1 s F ( s ), from Theorem 6.17, property 5. The result follows.

0

4. L [u a ( x ) f ( x a)] = e as L [f ( x )] = e as F ( s ), from Theorem 6.19.

The result follows.

a s F ( s ), from Theorem 6.19. The result follows. Example 6.29. Find L

Example 6.29. Find L 1 [

Solution

1

s ( s 2 + 1) ].

We can write

1

+ 1) = 1 s F ( s ), where F ( s ) =

s

( s 2

1 + 1 . Then

s

2

f ( x ) = L 1 [F ( s )] = sin x , so we get

L 1 [

+ 1) ] = L 1 [ 1 s F ( s )] = x f ( t ) dt = x sin t dt = 1 cos x.

1

0

0

s

( s 2

] = L − 1 [ 1 s F ( s )] = x f (

Math 334

6.3. INVERSE LAPLACE TRANSFORMS

92

Example 6.30. Find L 1 [

1

s ( s 2 + +2 s + 5) ].

Solution

Example

Solution

L 1 [

s ( s 2 + 2 s + 5) ] = L 1 [ ( s + 1) 2 + 4 ] = e x L 1 [ s 2 + 4 ] = 1

1

1

1

2 e x sin 2 x.

6.31. Find

L 1 [ 1 + e s ].

s

2

L 1 [ 1 + e s

s

2

] = L 1 [

2 + e s 2 ] = L 1 [ 2 ] + L 1 [ e

s

s

1

s

1

s 2 ]

s

= x + u 1 ( x )( x 1) .

Example 6.32. Find L 1 [

Solution

4

e

2s

s 2 + 16 ].

L 1 [

4

e 2s

s 2

4

+ 16 ] = L 1 [e 2s · s 2 + 16 ] = u 2 ( x ) L 1 [ s 2 +

4

16 ] = u 2 ( x ) sin 4 x.

Many transforms that one encounters are of the form F ( s ) = P ( s ) , where P and Q are polynomials in s

with deg { Q } > deg { P } . To evaluate L 1 [F ( s )], one writes

( s

)

Q

P

( s

Q

( s

)

)

in terms of partial fractions.

Example 6.33 (distinct linear factors) . Find

Solution We write the expression in the form

L 1 [

7 s 1 ( s + 1)( s + 2)( s 3) ].

7 s 1

A

B

C

 

( s + 1)( s + 2)( s 3) = s + 1 + s + 2 +

s

3 .

Solving for the constants yields: A = 2, B = 3, and C = 1. Thus, we get

L 1 [

7 s 1 ( s + 1)( s + 2)( s 3) ] = L 1 [

s + 1 ] L 1 [ s + 2 ] + L 1 [ s 3 ] = 2 e x 3 e 2x + e 3x .

2

3

1

Example 6.34 (repeated linear factors) . Find L 1 [

Solution We write the expression in the form

s 2 + 9 s + 2 ( s 1) 2 ( s + 3) ].

s 2 + 9 s + 2

A

B

C

( s 1) 2 ( s + 3) = s 1 + ( s 1) 2 + s + 3 .

Solving for the constants yields: A = 2, B = 3, and C = 3. Thus, we get

L 1 [

s 2 + 9 s + 2 ( s 1) 2 ( s +

3) ] = L 1 [ s 1 ] + 3 L 1 [

2

1

1) 2 ] L 1 [ s + 3 ] = 2 e x + 3 xe x e 3x .

1

( s

Math 334

6.4. APPLICATIONS TO DIFFERENTIAL EQUATIONS

93

Example 6.35 (quadratic factors) . Find L 1 [

Solution We write the expression in the form

2 s 2 + 10 s

s 2 2 s +

5 ( s + 1)].

L

1 [

2 s 2 + 10 s 5 ( s + 1)] = A ( s 1) + B

s 2 2 s +

C

( s 1) 2 + 4 + s + 1 .

Solving for the constants yields: A = 3, B = 8, and C = 1. Thus, we get

L

1 [

2 s 2 + 10 s s 2 2 s +

5 ( s + 1)] = 3 L 1 [

s 1 ( s 1) 2

4 ] + 4 L 1 [

+

( s 1) 2 + 4 ] L 1 [ s + 1 ]

2

1

= 3 e x cos 2 x + 4 e x sin 2 x e x .

x cos 2 x + 4 e x sin 2 x − e − x .

6.4 Applications to Differential Equations

The easiest way to see how to apply Laplace transforms to diffe rential equations is to work through some examples.

Example 6.36. Solve the following initial value problem:

y y = 2 x,

y (0) = 1 ,

y (0) = 2 .

Solution Method 1 (the old approach) First solve the homogeneous equation: y y = 0.

=

Now look for a particular solution: y p ( x ) = x ( Ax + B ) = Ax 2 + Bx . Plug into the DE to get

y = e rx

=

r 2 r = 0

r = 0 , 1

=

y h ( x ) = c 1 + c 2 e x .

′′

p

y

y p = 0

=

2 A B = 0

2 A = 2

=

Thus, we have

y ( x ) = c 1 + c 2 e x x 2 2 x,

Apply the initial conditions:

y (0) = 2 1 y (0) =

=

c 1 +

c 2 = 2 1

c 2 2 =

=

A = 1

B = 2

=

y p ( x ) = x 2 2 x.

y ( x ) = c 2 e x 2 x 2 .

c 1 = 1 c 2 = 0

=

y ( x ) = 1 x 2 2 x .

Method 2 (using Laplace transforms) Take Laplace transforms of the DE:

L [y ] L [y ] = 2 L [x ]

=

=

=

s 2 Y ( s ) sy (0) y (0) [sY ( s ) y (0)] = 2

s

2

s 2 Y ( s ) s + 2 sY ( s ) + 1 = 2

Y ( s ) = s 3 3 s 2 + 2 s 3 ( s 1)

s

2

= ( s 1)( s 2 2 s 2) s 3 ( s 1)

= 1 s 2

s

2 2

s

3

Math 334

6.4. APPLICATIONS TO DIFFERENTIAL EQUATIONS

94

Finally, taking the inverse Laplace transform, we arrive at the final solution:

y ( x ) = L 1 [Y ( s )] = 1 2 x x 2 .

L − 1 [ Y ( s )] = 1 − 2 x − x 2

Example 6.37. Solve the following initial value problem:

y 2 y + 5 y = 8 e x ,

y (0) = 2 ,

y (0) = 12 .

Solution Take Laplace transforms of the DE:

L [y ] 2 L [y ] + 5 L [y ] = 8 L [e x ]

=

=

=

=

s 2 Y ( s ) sy (0) y (0) 2 [sY ( s ) y (0)] + 5 Y ( s ) = 2

s

2

s 2 Y ( s ) 2 s 12 2 sY ( s ) + 4 + 5 Y ( s ) = s 8 + 1

2 s 2 + 10 s ( s 2 2 s + 5)( s + 1) ( s 1)

Y ( s ) =

Y ( s ) = 3

2

1

( s 1) 2 + 4 4 ( s 1) 2 + 4

s

+ 1 .

Finally, taking the inverse Laplace transform, we arrive at the final solution:

y ( x ) = 3 e x cos 2 x + 4 e x sin 2 x e x .

x cos 2 x + 4 e x sin 2 x − e − x .

Example 6.38. Solve the following initial value problem:

y 2 y + 5 y = 8 e 7 x ,

y (7) = 2 ,

y (7) = 12 .

Solution It appears that we can not use Laplace transforms since L [y ] = sY ( s ) y (0), and we don’t know y (0). But we can get around this by moving the initial point (in this case x 0 = 7) to the origin by means of a translation.

Let t = x 7

and w ( t ) = y ( x ). Then we get

w ( t ) = y ( x ) ,

w ( t ) = y ( x ) ,

so, the initial value problem becomes

w 2 w + 5 w = 8 e t ,

w (0) = y (7) ,

w (0) = y (7) ,

w (0) = 2 ,

w (0) = 12 .

This is just the initial value problem we had in Example 6.40. The solution is

w ( t ) = 3 e t cos 2 t + 4 e t sin 2 t e t .

The solution to the original problem is

y ( x ) = w ( x 7) = 3 e x 7 cos[2( x 7)] + 4 e x 7 sin[2( x 7)] e (x 7) .

sin[2( x − 7)] − e − ( x − 7 ) . Next we consider

Next we consider an initial value problem with discontinuous forcing.

Math 334

6.4. APPLICATIONS TO DIFFERENTIAL EQUATIONS

95

Example 6.39. Solve the following initial value problem:

y + 4 y = g ( x ) ,

y (0) = 0 ,

y (0) = 0 ,

where g ( x ) =

  

1

1 1 < x < 2 .

0 x > 2

0 < x < 1

Solution We can re-write g as follows: g ( x ) = 1[u 0 ( x ) u 1 ( x )] 1[u 1 ( x ) u 2 ( x )] = u 0 ( x ) 2 u 1 ( x ) + u 2 ( x ). we have

G ( s ) = L [g ( x )] =

L [u 0 ( x )] 2 L [u 1 ( x )] + L [u 2 ( x )] = 1 s 2 e s

s

+ e 2s

s

.

Take Laplace transforms of the DE:

L [y ] + 4 L [y ] = L [g ( x )]

=

=

=

=

s 2 Y ( s ) sy (0) y (0) + 4 Y ( s ) = G ( s )

s 2 Y ( s ) + 4 Y ( s ) = G ( s )

Y ( s ) =

G

( s )

1

e

s

e

2s

s 2 + 4 = s ( s 2 + 4) 2 s ( s 2 + 4) + s ( s 2 + 4)

Y ( s ) = F ( s ) 2 e s F ( s ) + e 2s F ( s ) ,

where

Thus,

F ( s ) =

1

= 1 4

s ( s 2 + 4)

1

s

s

2

s + 4 .

1

f ( x ) = L 1 [F ( s )] = 4 (1 cos 2 x ) .

Then

Finally, taking the inverse Laplace transform, we arrive at the final solution:

y ( x ) = L 1 [Y ( s )] =

L 1 [F ( s )] 2 L 1 [e s F ( s )] + L 1 [e 2s F ( s )]

= f ( x ) 2 u 1 ( x ) f ( x 1) + u 2 ( x ) f ( x 2)

1

= { 1 cos 2 x 2 u 1 ( x )(1 cos[2( x 1)]) + u 2 ( x )(1 cos[2( x 2)]) } .

4

Now we consider an ODE with variable coefficients.

} . 4 Now we consider an ODE with variable coefficients. Example 6.40. Solve the following

Example 6.40. Solve the following initial value problem:

y + 2 xy 4 y = 1 ,

y (0) = 0 ,

y (0) = 0 .

Solution Take Laplace transforms of the DE:

L [y ] + 2 L [xy ] 4 L [y ] = L [1]

=

=

=

s 2 Y ( s ) sy (0) y (0) 2 ds [ sY ( s ) y (0)] 4 Y ( s ) = 1

s

d

s 2 Y ( s ) 2[sY ( s ) + Y ( s )] 4 Y ( s ) = 1

s

Y ( s ) + 3 s

s

2 Y ( s ) = 1

2 s 2 .

Math 334

6.5. CONVOLUTION

96

This is a linear ODE in Y ( s ). Look for an integrating factor µ:

µ

µ

s

= 3 s 2

=

ln µ = 3 ln s s 2

4

The ODE for Y becomes:

ds [µY ( s )] = µ Y ( s ) + µ Y ( s ) =

d

µ

µ = s 3 e s 2 / 4 .

s

2 e s 2 / 4 .

=

µ

2 s 2 =

Integrating yields:

µY ( s ) = 2 e s 2 / 4 ds = e s 2 / 4 + C

s

=Y ( s ) = 1

C

s 3 + s 3

e

s 2 / 4 .

It remains to determin the value of the constant if integration C . There is no auxiliary condition inherited from the original ODE. To get an appropriate condition to enable us to determine C , we utilize Theorem 6.12 that states that Y ( s ) 0 as s → ∞. Therfore

Y ( s ) = 0

lim

s

=

C = 0

=

Y ( s ) = s 1 3 .

Finally, taking the inverse Laplace transform, we arrive at the final solution:

y ( x ) = L 1 [ 3 ] = x 2

1

s

2 .

y ( x ) = L − 1 [ 3 ] = x 2 1 s

We can summarize the application of Laplace transforms to differential equations as follows.

1. For an ODE with constant coefficients, the equation for the L aplace transform is of the form AY = B .

2. For an ODE with polynomial coefficients in x , the equation for the Laplace transform is an ODE with polynomial coefficients in s .

3. If the coefficient functions of the ODE are liear in x , the ODE for Y is a first order ODE.

4. The auxiliary condition to use when solving a first order ODE in Y is lim

s

Y ( s ) = 0.

6.5 Convolution

Consider the following initial value problem:

y + y = g ( x ) ,

y (0) = y (0) = 0 .

Take the Laplace transform of the equation to get:

s 2 Y ( s ) sy (0) y (0) + Y ( s ) = G ( s )

=

Y ( s ) = s G 2 ( + s ) 1 = F ( s ) G ( s ) ,

where F ( s ) =

1

s 2 + 1 .

We would like to express the solution y ( x ) in terms of f ( x ) and g ( x ), i.e. we would like to express L 1 [F ( s ) G ( s )] in terms of L 1 [F ( s )] and L 1 [G ( s )]. To do this, we define a special type of product of functions. Let f, g P C (0 , ).

Math 334

6.5. CONVOLUTION

97

Definition 6.41. The convolution of f and g , denoted f g , is defined as:

( f g )( x ) := x f ( x t ) g ( t ) dt.

0

Example 6.42.

(1)

(2)

1 x = x 1 · t dt = x 2 2

0

.

x x 2 = x ( x t ) · t 2 dt = x 12 4 .

0

Theorem 6.43.

t ) · t 2 dt = x 12 4 . 0 Theorem 6.43. The convolution

The convolution product satisfies the following properties :

1.

2. ( g + h ) = f g + f h ;

3. ( g h ) = ( f g ) h ;

4. f 0 = 0 .

f g = g f ;

f

f

(convolution product is commutative)

(convolution product is distributive over addition)

(convolution product is associative)

Proof

Exercise.

(convolution product is associative) Proof Exercise. Remark. While the convolution product has many of the

Remark. While the convolution product has many of the properties of o rdinary multiplication of functions, it different in that it has no multiplicative identity element, i.e. there is no function g with the property that

g f = f for all funtions f .

Theorem 6.44.

If

(i) f, g P C (0 , ) ;

 

(ii)

F ( s ) = L [f ( x )] and G ( s ) = L [g ( x )], then

 
 

L [f g ] = F ( s ) G ( s ) ,

or equivalently

L 1 [F ( s ) G ( s )] =

Proof

( f g )( x ) .

L [f g ] = e sx ( f g )( x ) dx =

0

0

e sx x

0

=

0

t

e sx f ( x t ) g ( t ) dx dt =

0

=

e sξ f ( ξ ) e st g ( t ) dt

0

0

f ( x t ) g ( t ) dt dx

0

e s (ξ + t ) f ( ξ ) g ( t ) dξ dt

=

F ( s ) G ( s ) .

f ( ξ ) g ( t ) dξ dt = F ( s ) G

1

s ( s 2 + 4) ].

Example 6.45. Find L 1 [

Solution Method 1 (the old approach)

L 1 [

Method 2 (using convolution)

s ( s 2 + 4) ] = L 1 [ 1

1

4 1

s + 4 ] = 1 4 (1 cos 2 x ) .

s s 2

Math 334

6.6. THE DELTA FUNCTION

98

L

1 [

1

s ( s 2 + 4)

]

= 2 L 1 [ 1

1

s ] L 1 [

s 2 + 4 ] = 2 x

2

1

0

L 1 [ 1 s ]( x t ) L 1 [

2

4 ]( t ) dt

s

2

+

=

1 x
2

0

1 · sin 2 t dt = 1 4

x

cos 2 t = 4 (1

0

1

cos 2 x ) .

1 4 x cos 2 t = 4 (1 − 0 1 cos 2 x )

Now, returning to the origin problem:

y + y = g ( x ) ,

y (0) = y (0) = 0 .

The solution satisfies:

y ( x ) = L 1 [

G ( s )

s 2 +

1 ] = g sin x = x

0

g ( t ) sin( x t ) dt.

Example 6.46. Solve the following integro-differential equation:

y ( x ) = 1 e 2x x y ( t ) e 2t dt,

0

y (0) = 1 .

Solution The equation may be written as

y = 1 x j ( t ) e 2(x t ) dt = 1 y e 2x .

0

Taking Laplace transforms we get

sY ( s ) y (0) = 1

s

Y ( s )

s +

2

=

Y ( s ) =

s + 2

2 s

1

s + 1

s ( s + 1) =

=

6.6 The Delta Function

y ( x ) = 2 e x .

6.6 The Delta Function y ( x ) = 2 − e − x . Mechanical

Mechanical systems are often acted upon by external forces t hat are large in magnitude but are of short duration. Some typical example are: a hammer hitting a nail; a bat hitting a baseball. These forces are of the form

  0 t < t 0  F ( t ) = ( ·
 0
t < t 0
F ( t ) =
( ·
·
·
)
t 0 t t 1 .
 
t > t 1
0
y
y=F(t)
t
t
t
0
1

Figure 6.4: A plot of a localized force y = F ( t ).

Math 334

6.6. THE DELTA FUNCTION

99

The integral of the force acting over an interval of time ic ca lled “impulse:” I = F ( t ) dt . From Newton’s

Law, F = ma, we get

t

1

t

0

t

I =

t

0

1

t

F ( t ) dt =

t

0

1

m dv

dt

dt = mv ( t 1 ) mv ( t 0 )

(i.e. impulse = change in momentum).

Consider an impulse over shorter and shorter time intervals .

v t t t 0 1
v
t
t
t
0
1
v t t t 0 1
v
t
t
t
0
1
shorter time intervals . v t t t 0 1 v t t t 0 1

v

shorter time intervals . v t t t 0 1 v t t t 0 1

t 0 t 1

. v t t t 0 1 v t t t 0 1 v t 0

t

F t t t 0 1
F
t
t
t
0
1
F t t t 0 1
F
t
t
t
0
1
F t t 0 t 1
F
t
t
0 t
1

Figure 6.5: A plot of a localized force and impulse for decrea sing time intervals.

The exact nature of the force in the interval [t 0 , t 1 ] is frequently unknown. What usually is known is the state of the system before and after the application of the fo rce. These duration of the force is often so short, that it is convenient to think of the force as acting instanta neously.

Math 334

6.6. THE DELTA FUNCTION

100

v t t t 0 1
v
t
t
t
0
1
F t t t 0 1
F
t
t
t
0
1

Figure 6.6: A plot of a localized force and impulse with simplified approximation.

We define the following functions:

δ h ( t ) =

|t | h

  |t | > h

1

2

0

h

for h 0 .

t
t
t
t
t
t
t
t
t
t
t
t
t
t
t
t
t
t
t
t
t
t
t

t

-h

h

Figure 6.7: A plot of a δ h ( t ).

Thes functions have the following property:

−∞ δ h ( t ) dt =

h

h

1

2

h

dt = 1 h ( h ( h )) = 1 .

2

Definition 6.47. The Dirac Delta Function is defined implicitly by the following properties:

1. δ ( t ) = 0 for t = 0;

2.

−∞

δ ( t ) = 1.

Remark. The Dirac delta function is not a function in the usual sense. However, one can “think” of it a s follows:

δ ( t ) = lim 0 δ h ( t ) =

h

0

t = 0 t = 0 .

Math 334

6.6. THE DELTA FUNCTION

101

Theorem 6.48. If f is continuous on ( −∞, ) , then for any c R ,

−∞

f ( t ) δ ( t c ) dt = f ( c ) .

Proof

We have

Therefore

δ h ( t c ) =

1

2

0

h

|t c | h

h

|t c | >

=

  c h t c + h

|t c | > h

1

2

0

h

.

−∞

h 0

−∞